2001
DOI: 10.1039/b009093j
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of heroin profiling using trace organic impurities

Abstract: The acidic and neutral impurities in heroin samples (46 Purified South-East Asian (PSEA) and 8 non-PSEA samples) were analysed using gas chromatography. Mass spectral detection allowed the construction of a comprehensive library of over 649 impurities. A variety of statistical procedures were used to select 70 viable profiling parameters. Cluster analyses were used to investigate the similarities between samples using organic parameters. A blended PSEA profile was constructed for comparison with samples of unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…These compounds are well resolved and present in sufficient quantities to allow detection using the current Australian National Heroin Signature Program GC-MS procedure for trace organic analysis (see Section 2) [5]. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds are well resolved and present in sufficient quantities to allow detection using the current Australian National Heroin Signature Program GC-MS procedure for trace organic analysis (see Section 2) [5]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In an HSP, seized samples are analyzed by a number of different analytical procedures with the aim of providing crucial drug trafficking and distribution intelligence information. HSP's typically analyze and evaluate major synthetic impurities and adulterants, and these approaches have been extensively researched and previously reported [1,[4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For sample clustering, the former does not require the knowledge of sample origin, whereas the latter is usually trained with samples of known origins. Related studies in this area are available in the literature 6,10,11 .…”
Section: Data Pretreatment For Chemometric Proceduresmentioning
confidence: 99%
“…Literature detailing analytical methods for the profiling of trace organic impurities abounds [3][4][5][6][7][8] and most of these methods are able to extract a very high number of impurities. For instance, Allen et al and Morello et al have successfully identified more than 30 acidic impurities from a single extract 4,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the 1980's, many studies have been conducted to determine chemical links between heroin exhibits [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%